Efficacy of Group Music Therapy Based on Emotion-Regulation Skills on Male Inpatients With Alcohol Dependence: A Randomized, Controlled Pilot Trial - Huang, Yi; Chen, Xu (Frontiers in Psychology, 2021)
Objective: This study aimed to determine the benefits and feasibility of using group music therapy based on emotion-regulation skills to treat male inpatients with alcohol dependence. Methods: We recruited male inpatients with alcohol dependence and randomly assigned those eligible for enrollment to either the study group or the control group. The study group received group music therapy along with treatment-as-usual, while the control group received only treatment-as-usual. Primary outcomes, including anxiety levels, sleep quality, and alcohol craving, were assessed at baseline and after 2 weeks of treatment. Secondary outcomes included feasibility measures such as dropout rates. We evaluated the acceptability of group music therapy based on semi-structured interviews and feedback from patients and therapists. Results: The average attendance rate of the study group patients who underwent group music therapy was 70.77%, and the drop-out rate was 7.69%. Based on intention-to-treat analysis, we found no differences in baseline assessments (p > 0.05). Assessment after 2 weeks of treatment showed that study group patients were less anxious, slept better, and had reduced alcohol cravings than control group patients. However, these differences were not statistically significant. Participants reported that group music therapy made them feel more relaxed and improved their mood. Conclusion: Group music therapy based on emotion-regulation skills is feasible with potential for efficacy and can be used to treat men with alcohol dependence in a closed inpatient environment. Further long-term research is required to gain a better understanding of the efficacy of using group music therapy to treat alcohol dependence.